Sentimen Analisis Inisiatif Vaksin Nasional Menggunakan Naïve Bayes dan Laplacian Smoothing Pada Komentar Video Youtube - Udayana, I Putu Agus Eka Darma; Sudipa, I Gede Iwan; Risaldi, Risaldi (Prahasta Publisher, 2022)
COVID-19 pandemic that has been declared by who in march 2020 Has been Indonesia biggest health crisis end in the decade. WHO said one of the quickest way to end the pandemic is through immunity through vaccine thu's theory is a national vaccine program initiated by the government in the middle of 2021. YouTube is of de facto public space in Indonesia cyberspace for its netizen for various conversation. from gossiping to discuss in public policy YouTube has been a gold mine for social media data mining enthusiast since 2010. but has been not utilized much by Indonesia Academic. do lack of popularity compared to Twitter which has been a media darling what Indonesian Acdemic ever since This research is focused on sentiment analysis pantydeal YouTube about the national vaccine initiation on a news channel in YouTube. This research is primarily consist of naive bayes classifier a a popular algorithm Indonesian data mining enthusiast which has some limitation such as the problem known as zero probability problem and also the use of non-public data which can be fixed by the use of Laplacian smoothing algorithm which when tested Using 100 of random comments as a data testing has resulted in 71% percent of succes rate and when we do a statistical analysis the precision , recall rate and the F-meassurement score of the classifier all resulted in above 75% score which is satisfactory.